2000
DOI: 10.1038/sj.cdd.4400673
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid-dependent growth inhibition, differentiation and apoptosis in acute promyelocytic leukemia cells. Expression and activation of caspases

Abstract: In the NB4 model of acute promyelocytic leukemia (APL), ATRA, 9-cis retinoic acid (9-cis RA), the pan-RAR and RARaselective agonists, TTNPB and AM580, induce growth inhibition, granulocytic differentiation and apoptosis. By contrast, two RXR agonists, a RARb agonist and an anti-AP1 retinoid have very limited activity, ATRA-and AM580-dependent effects are completely inhibited by RAR antagonistic blockade, while 9-cis RA-induced cell-growth-inhibition and apoptosis are equally inhibited by RAR and RXR antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 42 publications
2
63
0
Order By: Relevance
“…Pharmacological inhibitors of p38a enhance retinoid-dependent growth inhibition and differentiation of AML cells We evaluated the consequences of p38a inhibition on ATRAinduced growth suppression and myeloid differentiation 36 of the APL-derived NB4 cell line, 31 which expresses the specific PML-RARa fusion product as well as the product of the normal RARa allele. Although inhibition of p38a by PD169316 (10 mM) exerted minor effects on the growth of NB4 cells, it enhanced the antiproliferative action of ATRA at sub-optimal concentrations (Figure 1a, left).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological inhibitors of p38a enhance retinoid-dependent growth inhibition and differentiation of AML cells We evaluated the consequences of p38a inhibition on ATRAinduced growth suppression and myeloid differentiation 36 of the APL-derived NB4 cell line, 31 which expresses the specific PML-RARa fusion product as well as the product of the normal RARa allele. Although inhibition of p38a by PD169316 (10 mM) exerted minor effects on the growth of NB4 cells, it enhanced the antiproliferative action of ATRA at sub-optimal concentrations (Figure 1a, left).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] We and others have shown that ATRA induces maturation followed by apoptosis in a variety of different cell lines. [5][6][7][8] Differentiation induced by binding of ATRA to its nuclear retinoid receptors is detectable within 24-48 h 9 followed by apoptosis at 72-96 h. 5 It has been shown that mitochondria play an important regulatory role in ATRA-induced apoptosis. In this case, activation of proapoptotic Bcl-2 family proteins, such as Bid and Bax, results in permeabilization of the outer mitochondrial membrane and cytochrome c release.…”
Section: Introductionmentioning
confidence: 99%
“…All-trans-retinoic acid (ATRA) is a naturally occurring vitamin A derivative that functions as a regulator of gene transcription (Umosono et al, 1988;Gianni et al, 2000;Duprez et al, 2003). ATRA interacts with members of the hormone receptor superfamily including the retinoic acid receptor (RAR) and the retinoid X receptor (RXR) (Sun and Lotan, 2002).…”
Section: Introductionmentioning
confidence: 99%